The Associations of Dyadic Coping and Relationship Satisfaction Vary between and within Nations: A 35-Nation Study - Hilpert, Peter; Randall, Ashley K.; Sorokowski, Piotr; Atkins, David C.; Sorokowska, Agnieszka; Ahmadi, Khodabakhsh; Alghraibeh, Ahmad M.; Aryeetey, Richmond; Bertoni, Anna; Bettache, Karim; Błażejewska, Marta; Bodenmann, Guy; et al. (Frontiers in Psychology, 2016)
Objective: Theories about how couples help each other to cope with stress, such as the systemic transactional model of dyadic coping, suggest that the cultural context in which couples live influences how their coping behavior affects their relationship satisfaction. In contrast to the theoretical assumptions, a recent meta-analysis provides evidence that neither culture, nor gender, influences the association between dyadic coping and relationship satisfaction, at least based on their samples of couples living in North America and West Europe. Thus, it is an open questions whether the theoretical assumptions of cultural influences are false or whether cultural influences on couple behavior just occur in cultures outside of the Western world. Method: In order to examine the cultural influence, using a sample of married individuals (N = 7,973) from 35 nations, we used multilevel modeling to test whether the positive association between dyadic coping and relationship satisfaction varies across nations and whether gender might moderate the association. Results: Results reveal that the association between dyadic coping and relationship satisfaction varies between nations. In addition, results show that in some nations the association is higher for men and in other nations it is higher for women. Conclusions: Cultural and gender differences across the globe influence how couples’ coping behavior affects relationship outcomes. This crucial finding indicates that couple relationship education programs and interventions need to be culturally adapted, as skill trainings such as dyadic coping lead to differential effects on relationship satisfaction based on the culture in which couples live.